2003
DOI: 10.1046/j.1432-1033.2003.03394.x
|View full text |Cite
|
Sign up to set email alerts
|

Trophoblast‐like human choriocarcinoma cells serve as a suitable in vitro model for selective cholesteryl ester uptake from high density lipoproteins

Abstract: As human choriocarcinoma cells display many of the biochemical and morphological characteristics reported for in utero invasive trophoblast cells we have studied cholesterol supply from high density lipoproteins (HDL) to these cells. Binding properties of 125I‐labeled HDL subclass 3 (HDL3) at 4 °C were similar for BeWo, JAr, and Jeg3 choriocarcinoma cell lines while degradation rates at 37 °C were highest for BeWo. Calculating the selective cholesteryl ester (CE)‐uptake as the difference between specific cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 73 publications
1
25
1
Order By: Relevance
“…In addition, BeWo cells express the LDL receptor and SR-BI, as do placental cells (75,76). However, these data are not in agreement with a recent study suggesting that BeWo cells do not express SR-BI (57). The discrepancy between studies could be due to the b30 subclone of BeWo cells or to the specificity of the different antibodies used for protein detection in the two studies.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…In addition, BeWo cells express the LDL receptor and SR-BI, as do placental cells (75,76). However, these data are not in agreement with a recent study suggesting that BeWo cells do not express SR-BI (57). The discrepancy between studies could be due to the b30 subclone of BeWo cells or to the specificity of the different antibodies used for protein detection in the two studies.…”
Section: Discussioncontrasting
confidence: 77%
“…1A) (57). The presence of a larger protein was expected, because previous studies have demonstrated that human SR-BI from villous trophoblast migrates with a molecular mass slightly higher than that of rodent SR-BI (55), and the human protein sequence is 43 amino acids longer than that of the mouse.…”
Section: Model Appropriatenessmentioning
confidence: 93%
“…Similarly, JAR cell is a placental choriocarcinoma cell line and placenta is known to produce various steroid hormones that are circulated to fetus as well as to the mother (Strauss et al 1996). JAR cells are ER-positive cell line and have been previously used for steroid hormone-related studies (Wadsack et al 2003). Thus, overexpression of HOXC10 in breast carcinoma tissue and also in JAR, MCF7, and T47D cell lines indicated that HOXC10 is potentially regulated by estrogen.…”
Section: Hoxc10 Is Overexpressed In Breast Cancer Tissue and Placentamentioning
confidence: 99%
“…Since cells from human choriocarcinoma display many of the biochemical and morphological characteristics reported for in utero invasive trophoblast cells (Wadsack et al 2003), these cell lines are more commonly used as a model that mimics the placental barrier. Utoguchi et al (2000) have been able to show that, in BeWo monolayers, the basolateral to apical transport of known p-glycoprotein substrates, vinblastin, vincristine and digoxin, is signifi cantly greater than transport to opposite direction.…”
Section: Cell Lines From Human Placentamentioning
confidence: 99%